1981
DOI: 10.1002/1097-0142(19810115)47:2<360::aid-cncr2820470225>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carcinoma—a retrospective review of patients less than thirty years of age: A report from childrens cancer study group

Abstract: Data from 119 patients with nasopharyngeal carcinoma who were under 30 years of age were retrospectively analyzed by the investigators of the Children's Cancer Study Group. The overall five-year survival and relapse-free survival rates from diagnosis were 51 and 36%, respectively. When the tumor was confined to the nasopharynx (1 + T2, 41 patients), the five-year survival was 75%. No significant correlation was found between survival or local recurrence and the radiation dose to the primary site. The five-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
37
1
8

Year Published

1985
1985
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 20 publications
12
37
1
8
Order By: Relevance
“…Actuarial disease-free and distant metastasis-free survivals are also significantly longer in our patients younger than 17, which draw a parallel to earlier series defining the same fact [2]. However, previously reported prognostic factors for locoregional control, such as Tstage [35], N-stage [37], total irradiation dose [37,38], and delays in radiotherapy delivery time [16,39] were not found to be significant in our series due to excellent loco-regional control.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Actuarial disease-free and distant metastasis-free survivals are also significantly longer in our patients younger than 17, which draw a parallel to earlier series defining the same fact [2]. However, previously reported prognostic factors for locoregional control, such as Tstage [35], N-stage [37], total irradiation dose [37,38], and delays in radiotherapy delivery time [16,39] were not found to be significant in our series due to excellent loco-regional control.…”
Section: Discussionsupporting
confidence: 84%
“…Twenty-four percent crude rate of our institutionally treated nasopharynx patients were 30 years old, mainly owing to being a tertiary reference center. Nasopharyngeal carcinoma in the young most commonly presents as advanced locoregional disease and early stage disease is generally around 12% or fewer in previously reported series [2,3,6,10,35,36]. Along with the literature, stage I and II patients only constitute 13.6% of our cohort.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Despite good local tumor control after highdose radiation therapy, treatment in many patients fails due to locoregional or systemic relapse and long-term survival is unsatisfactory. Most relapses occur within the first 2 years (median of 8 months) and more than 50 % of patients who relapse have overt distant metastases [11,18,25]. With exclusive radiotherapy, the 5-year survival rate has been reported as 20-60 % in most series of young patients affected by NPC [18,19,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Several publications reported that the majority of disease recurrences were either outside the margin or at the margin of the treatment portals. 11,13,27,28 Patients usually present with the undifferentiated histologic type and with advanced locoregional disease at diagnosis, and distant metastasis becomes a major obstacle in curing children with nasopharyngeal carcinoma. Clearly, there is a need for early, effective, systemic therapy.…”
Section: Discussionmentioning
confidence: 99%